Groundwater quality assessment using the WQI and GIS mapping: Suitability for drinking and irrigation usage in the Sirdala block of Nawada district - Kumar, Abhishek; Maurya, Nityanand Singh (Water science & technology. Water supply, 2023)
In the present study, the suitability of groundwater for drinking and irrigation purpose were analyzed. A total of 65 groundwater samples were collected and analyzed for relevant water quality parameters from Sirdala block of Nawada district Bihar (India). To estimate the WQI for the drinking purpose, various parameters such as pH, TDS, TH, AS and major ions (Ca2+, Mg2+, Na+, K+, Cl−, F−, HCO3−, NO3−, SO42−) were considered. The WQI for irrigation, various irrigation indices namely soluble sodium percent (Na%), sodium adsorption ratio (SAR), residual sodium bicarbonate (RSCB), permeability index (PI), magnesium hazards ratio (MHR), Kelly's ratio (KR), potential salinity (PS), Cl−: HCO3−, Mg(2+): Ca(2+) and Na+: Ca(2+) were employed and discussed in addition with Wilcox and USSL diagram. Plots, namely Gibbs ratio and Piper diagram, were used to understand chemical characteristics of groundwater. The WQI for drinking purpose was observed between 57.67 and 929.90 in which most samples (70.76%) were unsuitable for drinking. However, the WQI for irrigation purpose varied from 87.88 to 434.67 in which 50% of samples were suitable. Gibb's plots determined in this study reveal that evaporation-precipitation was the dominant factor that influences hydrochemistry. Piper plots suggest that Na-HCO3− water type was major hydrochemical facies in groundwater.